Pseudoaneurysm of the Anterior Spinal Artery in a Patient with Moyamoya: An Unusual Cause of Subarachnoid Hemorrhage - Walz, D.M.; Woldenberg, R.F.; Setton, A. (American Journal of Neuroradiology, 2006)
SUMMARY: Subarachnoid hemorrhage (SAH) is a recognized presentation of Moyamoya disease in adults. Because there are extensive collateral networks and potential complications that develop, a thorough investigation of the intracranial and extracranial circulation is necessary to exclude a treatable cause when these patients present with SAH. We present a case of SAH due to a ruptured pseudoaneurysm of the anterior spinal artery arising from the supreme intercostal artery, which was the sole source of blood supply to the intracranial circulation.